The Diary of Queen Maria Carolina of Naples, 1781-1785 - Recca, Cinzia. author. aut Link
X, 412 p.
Keywords: This work offers a new portrayal of Queen Maria Carolina of Naples as a woman of power with weaknesses and ambitions, and analyzes the Queen's actions, from her political choices to her alliance and betrayals. A careful examination of the period (1781-1785) covered by the diary shows that the daily life of the Queen and offers key evidence of her political acumen and her personal relationships. Recca cross-analyses unpublished personal documents, which include the integral diary and private correspondence. The book focuses on the political influence that Queen Maria Carolina wielded beside her husband, King Ferdinand IV, and the criticism that has been made by contemporary historians and intellectuals who have often tended to discredit the sovereign for personal rather than political reasons. .